IMPACT ON SMART CLASS EDUCATION SYSTEM - S.GOPINATH, DR. SREEYA B (International Journal of Advanced Science and Technology, 2020)
Technology is a gift of god. After the Gift of life it’s perhaps the greatest of God’s gifts. It is the mother of civilizations, of art and science. Technology has certainly changed the way we live. It has impacted different facts of life and refined living. Undoubtedly, technology assumes a significant role in every sphere of life. Several manual facts can be automated, thanks to technology. Also, many critical processes can be carried out with the help of modern technology, and living has changed for the better. Technology has revolutionized the field of education. The significance of innovation in school cannot be ignored and overlooked. The main objective of this paper is to know about impact on smart class education system. The researcher adopted descriptive research method to carry out the research and followed convenient sampling method to collect the samples. The sample size is 150. The results observed from the analysis of the study shows that there are progressive impacts of modern technologies in education. The use of technology has made the process of teaching & learning more enjoyable.